The Role of Organizational Capabilities, Innovation, and Internal Control in Achieving Competitive Advantage: Evidence from Batik SMEs - Fitriyah Nurhidayah; Meutia; Rudi Zulfikar; Lia Uzliawati (Academic Bright Collaboration, 2026)
Purpose - This study aims to examine the effects of organizational capabilities on innovation, internal control, and competitive advantage in batik MSMEs, as well as to analyze whether innovation and internal control contribute to competitive advantage. Methods - This research adopts a quantitative explanatory design using a cross-sectional survey of 120 batik MSME owners and managers in Surakarta, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The measurement model was validated through Confirmatory Factor Analysis to ensure reliability and validity. Findings - The results show that organizational capability has a positive and significant effect on innovation (p = 0.005), competitive advantage (p = 0.001), and internal control (p < 0.001). However, innovation (p = 0.904) and internal control (p = 0.381) do not significantly influence competitive advantage. These findings indicate that competitive advantage is primarily driven by organizational capability rather than by innovation or internal control. Research Implications - The findings suggest that MSMEs should prioritize strengthening internal capabilities, including managerial competence and resource management, as the main strategy to enhance competitiveness. Innovation and internal control need to be aligned with strategic objectives to generate measurable competitive outcomes. Originality - This study provides empirical evidence that challenges the dominant assumption that innovation directly drives competitive advantage. By integrating the Resource-Based View, dynamic capabilities, and internal control perspectives, this study highlights the more fundamental role of organizational capability in culturally embedded MSMEs.